(Meta)ethics and legal philosophy - Zalewska, Monika (Hybris, 2014)
In this paper I have focused on methodological problems of ethics and legal philosophy. My main goal was to determine relation between meta-ethics and legal philosophy. In the first part I tried to describe historical context, how jurisprudence become independent form ethics. Then in second part I examined relations between main disciplines of ethics and legal philosophy pointing out that although there are some similarities, there is even more differences. Finally in the third part I explored relation between meta-ethics and legal philosophy. My conclusion was that the problems of meta-ethics also exists in legal philosophy but the level of significance is lower. The reason for it lays in the specific character of legal norms which existence depends on the will of competent authority in contrast to moral norms which need other, meta-ethical justification.